A model for capturing and tracing architectural designs - Roldán, M. Luciana (2006)
Software architecture constitutes the primary design of a software system. Consequently, architectural design decisions involved in architecture design have a key impact on the system in such aspects as future maintenance costs, resulting quality, and timeliness. However, the applied knowledge employed and the design decisions taken by software architects are not explicitly represented in the design despite their important role; consequently, they remain in the mind of designers and are lost with time. In this work, a model for capturing and tracing the products and architectural design decisions involved in software architecture design processes is proposed. An operational perspective is considered in which design decisions can be modelled by means of design operations. The basic ontology of situation calculus is adopted to formally model the evolution of a software architecture.